2016
DOI: 10.1158/1535-7163.mct-15-0737
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib against Esophageal or Head-and-Neck Squamous Cell Carcinoma: Significance of Activating Oncogenic HER4 Mutations in HNSCC

Abstract: The prognosis for patients with advanced esophageal or head-and-neck squamous cell carcinoma (ESCC or HNSCC) remains poor, and the identification of additional oncogenes and their inhibitors is needed. In this study, we evaluated the sensitivities of several ESCC and HNSCC cell lines to HER inhibitors (cetuximab, erlotinib, and afatinib) in vitro and found two cell lines that were hypersensitive to afatinib. Sequence analyses for the afatinib-targeted HER family genes in the two cell lines revealed that one ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Recently, mutations in the genes encoding other RTKs, such as FGFR1 or PDGFRA were found in CRC PDX models with intrinsic resistance to cetuximab (47). Nakamura et al also found HER4 mutation in cetuximabresistant ESCC or HNSCC cells (48). These RTK crosstalk mechanisms associated with resistance have also been reported in other tumors such as NSCLC, breast cancer or melanoma (49).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, mutations in the genes encoding other RTKs, such as FGFR1 or PDGFRA were found in CRC PDX models with intrinsic resistance to cetuximab (47). Nakamura et al also found HER4 mutation in cetuximabresistant ESCC or HNSCC cells (48). These RTK crosstalk mechanisms associated with resistance have also been reported in other tumors such as NSCLC, breast cancer or melanoma (49).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, mutations in the genes encoding other RTKs, such as FGFR1 or PDGFRA were found in CRC PDX models with intrinsic resistance to cetuximab (47). Nakamura et al also found HER4 mutation in cetuximab-resistant ESCC or HNSCC cells (48). These RTK crosstalk mechanisms associated with resistance have also been reported in other tumors such as NSCLC, breast cancer or melanoma (49).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting EGFR with EGFR tyrosine kinase inhibitors (TKi), such as ge tinib, erlotinib or afatinib, inhibits the proliferation of oesophageal cancer cell lines in vitro (15)(16)(17), but, clinical trials of EGFR inhibitors in oesophageal cancer, including ESCC, have shown mixed results. Monotherapy trials in unselected patients with EGFR inhibitors indicate that there is an EGFR-driven minority ESCC subgroup who gain survival, symptomatic control and health-related quality of life bene ts from EGFR inhibitors (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%